Disruption of Colorectal Cancer Network by Polyphyllins Reveals Pivotal Entities with Implications for Chemoimmunotherapy - Ram Siripuram; Zinka Bartolek; Ketki Patil; Saj S. Gill; S. Balakrishna Pai (Biomedicines, 2022)
The prevalence of colorectal cancer has increased world-wide with high rates of mortality and morbidity. In the absence of efficacious drugs to treat this neoplasia, there is an imminent need to discover molecules with multifaceted effects. To this end, we opted to study the effect of steroidal saponins such as Polyphyllins. We performed anticancer activity studies with three analogs of Polyphyllins: Polyphyllin D (PD), Polyphyllin II (PII) and Polyphyllin G (PG). Here we show the potent effect of PD, PII (IC50 of 0.5−1 µM) and PG (IC50 of 3 µM) in inhibiting the viability of colorectal adenocarcinoma cells (DLD-1) and colorectal carcinoma cells (HCT116). PD and PII also showed inhibition of cell proliferation and sustained response upon withdrawal of the compounds when assessed by clonogenic assays in both the cell lines. Elucidation of the molecular mode of action revealed impact on the programmed cell death pathway. Additionally, proteomic profiling of DLD-1 revealed pivotal proteins differentially regulated by PD and PII, including a downregulated peroxiredoxin-1 which is considered as one of the novel targets to combat colorectal cancers and an upregulated elongation factor 2 (EF2), one of the key molecules considered as a tumor associated antigen (TAA) in colon cancer. Entities of cell metabolic pathways including downregulation of the key enzyme Phosphoglycerate kinase 1 of the glycolytic pathway was also observed. Importantly, the fold changes per se of the key components has led to the loss of viability of the colorectal cancer cells. We envision that the multifaceted function of PD and PII against the proliferation of colorectal carcinoma cells could have potential for novel treatments such as chemoimmunotherapy for colorectal adenocarcinomas. Future studies to develop these compounds as potent anti-colorectal cancer agents are warranted.